Why only some plants emit isoprene. (19th October 2012) - MONSON, RUSSELL K.; JONES, RYAN T.; ROSENSTIEL, TODD N.; SCHNITZLER, JÖRG‐PETER
ABSTRACT Isoprene (2‐methyl‐1, 3‐butadiene) is emitted from many plants and it appears to have an adaptive role in protecting leaves from abiotic stress. However, only some species emit isoprene. Isoprene emission has appeared and been lost many times independently during the evolution of plants. As an example, our phylogenetic analysis shows that isoprene emission is likely ancestral within the family Fabaceae (= Leguminosae), but that it has been lost at least 16 times and secondarily gained at least 10 times through independent evolutionary events. Within the division Pteridophyta (ferns), we conservatively estimate that isoprene emissions have been gained five times and lost two times through independent evolutionary events. Within the genus Quercus (oaks), isoprene emissions have been lost from one clade, but replaced by a novel type of light‐dependent monoterpene emissions that uses the same metabolic pathways and substrates as isoprene emissions. This novel type of monoterpene emissions has appeared at least twice independently within Quercus, and has been lost from 9% of the individuals within a single population of Quercus suber. Gain and loss of gene function for isoprene synthase is possible through relatively few mutations. Thus, this trait appears frequently in lineages; but, once it appears, the time available for evolutionary radiation into environments that select for the trait is short relative to the time required for mutations capable of producing a non‐functional isoprene synthase gene. The high frequency of gains and losses of the trait and its heterogeneous taxonomic distribution in plants may be explained by the relatively few mutations necessary to produce or lose the isoprene synthase gene combined with the assumption that isoprene emission is advantageous in a narrow range of environments and phenotypes.